Campanhas de mobilização social em espaços públicos ampliados pela comunicação digital - Santos, Carlos Roberto Gomes dos (2018)
In this work, based on the theory of complexity of Edgar Morin, we study the communicative possibilities of social mobilization campaigns in contemporary societies, the so called net societies (CASTELLS), which have its public spaces amplified by the new tecnologies. Coherent whith the theory of complexity, we searched contributions from diferent kinds of disciplines in order to understand the communicative processes involved in the social mobization campaign implemented by Ministério Público do Trabalho - MPT against the labor law reform proposed by brazilian government. For this purpouse, we went through the history of MPT and its atributions, in order to understand the reasons that drove this government institution to place itself against the central governament positions related to the reform. We also studied the social moviments (GOHN, 2003; CASTELLS, 2013; ZIZEK, 2012), the ciberculture and the net society (CASTELLS, 2000, 2013; LÉVY, 2002, 2010; HAN, 2016, 2017), the different concepts of the term citzenship (MOUFFE, 1996; ARENDT, 2004; BOBBIO, 1994), the public communication (DUARTE, 2009, 2013; TORO; WERNECK, 1996). Finally, we analized the campaign implemented by MPT in the social media Facebook, which, in the period studied, reached 75.782 sharings, showing that its objectives of public engagement were achieved, a success step in mobilization campaigns. The campaign used a discourse of modalization of knowledge capable of driving to broad accession. Presenting its narrative in multiple platforms, the MPT performed a convergent campaign, mixing traditional and digital medias, promoting social conections and producing contents of easy sharing, which amplified the possibilities of extension to those who have no access to social media. However, associations between the campaign and influencers capable to redirect the posts to its public weren’t observed, as well as answers to public comments, using the Facebook tools, specific directions to the public participation in preventing the labor law changings and a future labour relations project which would summarise the objectives to be achieved.